2017
DOI: 10.1021/acs.biomac.7b00265
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Polymer and Quantum Dot Excipients to Facilitate siRNA Release and Self-Reporting of Disassembly in Stimuli-Responsive Nanocarrier Formulations

Abstract: The incorporation of anionic excipients into polyplexes is a promising strategy for modulating siRNA binding vs. release and integrating diagnostic capabilities; however, specific design criteria and structure-function relationships are needed to facilitate the development of nanocarrier-based theranostics. Herein, we incorporated poly(acrylic acid) (PAA) and quantum dot (QD) excipients into photolabile siRNA polyplexes to increase gene silencing efficiencies by up to 100% and enable self-reporting of nanocarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Figure 1 a reveals the uniform size distribution of GO nanosheets below 100 nm, with an average size of approximately 45 nm. The high electron density of GO exhibited better contrast compared to chitosan, which is barely visible due to its low electron density and hydrated nature [ 21 ]. Due to the higher surface area, nanoscale GO or reduced GO sheets have been widely used as drug carriers [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 a reveals the uniform size distribution of GO nanosheets below 100 nm, with an average size of approximately 45 nm. The high electron density of GO exhibited better contrast compared to chitosan, which is barely visible due to its low electron density and hydrated nature [ 21 ]. Due to the higher surface area, nanoscale GO or reduced GO sheets have been widely used as drug carriers [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The HRTEM images of BP-CDs/HER3 siRNA complexes demonstrated that the final nanocomplexes are spherical in morphology with good dispersity. The high electron density of N-CD cores exhibits better contrast compared to PEI polymers /siRNA, which are barely visible due to their low electron densities and hydrated nature [31]. The various dark objects identified within the BP-CDs/HER3 siRNA complex structure are ascribed to the presence of electrondense N-CDs.…”
Section: Her3 Sirna Transfection For Targeting Her2-overexpressing Bt...mentioning
confidence: 96%
“…While beneficial for systemic delivery, the high physiological resistance of fluorous interactions poses unique challenges for siRNA delivery because of the need to release the siRNA inside the target cells . A viable strategy to this conundrum that is proposed here is to exploit the easy intracellular degradation of disulfide bonds, which is the result of a 1000‐fold difference in the intracellular concentrations of glutathione (GSH) when compared with its low micromolar extracellular levels .…”
Section: Introductionmentioning
confidence: 99%